Causes of puerperal and neonatal sepsis in resource‐constrained settings and advocacy for an integrated community‐based postnatal approach. Issue 1 (5th July 2013) - Miller, Anne E.; Morgan, Christopher; Vyankandondera, Joseph
Abstract: Background: Puerperal sepsis and neonatal sepsis are important causes of mortality and morbidity in low‐income countries. Objectives: To help improve global guidelines on postpartum care by reviewing existing data on microbiologic causes of sepsis among mothers, newborns, and mother–newborn pairs. Search strategy: An extensive literature review of peer‐reviewed publications from resource‐constrained settings was conducted using PubMed. Selection criteria: Primary research studies containing microbiologic data on puerperal sepsis or combined maternal and neonatal sepsis published since 1980. Data collection and analysis: Study characteristics and results were analyzed. Data regarding causative microorganisms were tabulated and discussed in the main text. Main results: Diagnostic evaluation of microorganisms causing puerperal sepsis was difficult, with few studies linking microorganisms causing infection in individual mother–newborn pairs. The most frequent microorganisms associated with puerperal sepsis were Neisseria gonorrhoeae and Chlamydia trachomatis . The most frequent microorganisms associated with neonatal sepsis were Escherichia coli, Staphylococcus aureus, and Klebsiella species. Conclusions: Management tools for community‐based care of mothers with puerperal sepsis—including early detection, initiation of broad‐spectrum antibiotic treatment, and timely referral—should be added to those currently in use for neonatal sepsis. Further research is required to address acceptability, feasibility, and impact of community‐based presumptive treatment.